Analysis of inhibition of guava (Psidium guajava l.) leaf polyphenol on the protein oxidative aggregation of frozen chicken meatballs based on structural changes. (February 2023) - Nuerjiang, Maheshati; Li, Ying; Yue, Xiaoxiang; Kong, Baohua; Liu, Haotian; Wu, Kairong; Xia, Xiufang
Graphical abstract: Highlights: Guava leaf polyphenol exhibited high antioxidant activity. Guava leaf polyphenol inhibited the oxidative aggregation of myofibrillar protein. Guava leaf polyphenol improved structure stability of myofibrillar protein. Abstract: This study compared the effects of guava leaf polyphenol (GLP) on the aggregation and structural changes of myofibrillar proteins (MPs) from chicken meatballs, frozen for 6 months, with that of tea polyphenol (TP). The high antioxidation ability of 450 mg/L GLP was manifested by changes in 1, 1-diphenyl-2-picrylhydrazyl (DDPH), 2, 2-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity, and the ferric reducing antioxidant power (FRAP) in vitro . Compared with the control, the carbonyl, disulfide bond content, particle size, zeta potential and turbidity of sample with GLP decreased by 25.9 %, 17.7 %, 18.2 %, 11.4 % and 11.7 %, respectively, while the solubility of the sample, after freezing it for 6 months, increased by 14.8 %. Meanwhile, in sustaining the structural stability of MPs, the GLP-treated group exhibited better microstructure (scanning electron microscopy, SEM), lower free amino and sulfhydryl loss, higher α-helix structure and fluorescence intensity than the control. Our results showed that GLP significantly inhibited MP aggregation, and was superior to TP in terms of its particle size, solubility, and turbidity, sulfhydryl content ( P < 0.05 ). Overall, it was demonstrated that GLP has the potential to inhibit protein aggregation and enhance structural stability during frozen storage.